PENGARUH FLUKTUASI MUKA AIR TERHADAP DEBIT ALIRAN PADA SUNGAI KETUPAK PADA SAAT MUSIM PENGHUJAN - Yendri, Okma; Oemiati, Nurnilam; Muafi, Alaik Yahya (CANTILEVER, 2019)
The fluctuations in Ketupak river water affect the amount of inundation that occurs in G Dwijaya Village, Tugumulyo Subdistrict, Musi Rawas Regency.  The research aims to obtain a cross section of river channels to drain runoff water, so that runoff water due to maximum rainfall does not cause inundation.  the Ketupak river channel is unable to float the flow discharge that occurs during the rainy season, besides that there is also a lot of sediment, garbage, trunks and branches that interfere with ketupak river flow, so a re-dimension of the river channel needs to be done.  Based on the calculation of the Ketupak River discharge in the rainy season using the Chow formula method, flowrate (Q) is obtained at 5.22 m³ / sec.  From the results of calculations According to the 5-year rainfall data from 2012-2016, Q = 0.719 m³ / s, so when the rainy season the flow in the river becomes 5.94 m³ / sec (Q ≤ Q max), to meet Q max = equal to 5.94 m³ / sec, it is necessary to add a river cross-sectional area of 12.33 m² to 15.63 m² so that Q is obtained at 5.94 m³ / sec (Q ≥ Q max).